KEARIFAN LOKAL PENGELOLAAN LUBUK LARANGAN DI SUNGAI SUBAYANG UNTUK PENGEMBANGAN MODUL MATA KULIAH PENDIDIKAN LINGKUNGAN - Perdana, Ramadhani Fajar; ', Suwondo; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: A research was conducted to find out the Local Wisdom of Lubuk Larangan Management in Subayang River for the development of Environmental Education Course Module conducted in Gema Village, Tanjung Belit Village and Batu Songgan Village Kampar Kiri Hulu District Kampar Province Riau Province from November 2015 to February 2016. The research is used for the development of Environmental Education course module, in two stages namely the data collection stage and the module development stage. The main parameter in this research is the management of Lubuk Larangan in Kecamatan Kampar Kiri Hulu. The management component was developed from Law 32 Year 2009. Data collection using Focus Group Discussion (FGD) method, survey, interview, and literature study. Further data were collected on the Biological Factor of Lubuk Larangan. The results of the research indicate that the community has local wisdom in the management of Lubuk Larangan in Subayang River: (1) Planning, the community has the knowledge to select the lubuk along the Subayang River that will be used as Lubuk Larangan area; (2) Utilization, fish harvesting is allocated for community youth, ninik mamak, and for mosque construction; (3) Controlling, banning and myth in the Lubuk Larangan area; (4) Maintenance, conservation efforts; (5) Supervision, the community of the implementation of the principle of mutual cooperation which of course can not be separated from existing adat institutions; (6) Law Enforcement, communities along the Subayang river implement a system of fines and beliefs in Lubuk Larangan. The results of this study can be used as module of Environmental Education course.Keywords : Local Widom, Lubuk Larangan, Focus Group Discussion (FGD),Module